Determinants of Mental Well-being in Serbia - Vladimir, (Sociološki pregled, 2020)
In this paper we examined the determinants of mental well-being in Serbia. Mental well-being is defined as a state of well-being in which the individual realizes his or her own potential, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to his or her community. Although the studies from this field on nationally representative samples from other countries are widely present, they are entirely neglected in Serbia. We used nationally representative Serbian samples from 2011 and 2016 that come from the European Quality of Life Survey. The data indicate that mental well-being declines with age, especially among older woman categories. Second, subjective general health is the most significant determinant of mental well-being. Optimism about own future, feeling tense, and satisfaction with family life come next. We also examined trends of mental well-being in five-years between the two rounds of the survey and found its slight but statistically non-significant decline.
Keywords: Mental well-being; Serbia; European Quality of Life Survey, WHO-5 scale